1990
DOI: 10.1161/01.atv.10.5.703
|View full text |Cite
|
Sign up to set email alerts
|

Role of dying endothelial cells in transendothelial macromolecular transport.

Abstract: There are focal areas in the aorta wtth an enhanced endothelial permeability to macromolecules, as indicated by the focal uptake of the proteln-blndlng azo dye Evans blue In vivo. These areas exhibit high rates of endothelial cell turnover and a number of structural characteristics In en face endothelial morphology. To determine the relationship of endothelial cell death to macromolecular leakage at the level of individual endothelial cells, thoracic aortas of 12 adult male Sprague-Dawley rats were studied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 5 publications
3
57
0
1
Order By: Relevance
“…These findings have led to the hypothesis that complex flow patterns cause an accelerated EC turnover (including cell mitosis and death), such that the resulting leaky junctions between the ECs undergoing turnover cause an increase in the permeability of large molecules (e.g., LDL) across the endothelial layer (79). Our experimental studies have provided evidence that EC mitosis (12,44) and death (42) are associated with the leakage of macromolecules such as LDL and albumin on an individual cell basis. Studies performed in a number of laboratories, including our own, have shown that these events of accelerated EC turnover occur primarily in areas with disturbed blood flow, e.g., arterial branch points (15,43,60,72).…”
Section: Effects Of Local Shear Stress Pattern On Klf2 and Mcp-1 Exprmentioning
confidence: 85%
“…These findings have led to the hypothesis that complex flow patterns cause an accelerated EC turnover (including cell mitosis and death), such that the resulting leaky junctions between the ECs undergoing turnover cause an increase in the permeability of large molecules (e.g., LDL) across the endothelial layer (79). Our experimental studies have provided evidence that EC mitosis (12,44) and death (42) are associated with the leakage of macromolecules such as LDL and albumin on an individual cell basis. Studies performed in a number of laboratories, including our own, have shown that these events of accelerated EC turnover occur primarily in areas with disturbed blood flow, e.g., arterial branch points (15,43,60,72).…”
Section: Effects Of Local Shear Stress Pattern On Klf2 and Mcp-1 Exprmentioning
confidence: 85%
“…Various experimental (2,19,21,37,38) and computational (1, 13-15, 25, 31, 33, 40) studies have been conducted to comprehend the pathways and mechanisms governing LDL transport from the artery lumen into the arterial wall and within the arterial wall. There are two pathways of LDL transport through the endothelium: by vesicular transcytosis, which is regulated by receptors on the endothelial cells (30), and through leaky junctions, most of which are located at the sites of dying or replicating cells (18,19).…”
mentioning
confidence: 99%
“…Examination of animal tissue using electron microscopy following incubation with LDL has revealed the presence of vesicles containing LDL within cells that may deliver lipoproteins across the endothelium via transcytosis (28,31). Other studies have shown that cells in a state of turnover can allow large macromolecules, including LDL and albumin, to cross the endothelium through so-called "leaky junctions" (15)(16)(17)33). Little work has probed the transport of LDL across cultured endothelial monolayers that may serve as models for understanding and controlling transendothelial transport of LDL.…”
mentioning
confidence: 99%